جينالوجيا الدولة في الشرق الأوسط: بنية السلطة والمجتمع (مجلة الواحات للبحوث والدراسات, 2015)
Has always been a dual society and the state of the most important dialectical diodes most discussion at the thought of actually politicians, they are key components Aleghanonyan and conditions are the most important in the establishment of the state as is customary in international law. The subject of the state of the most important topics of political science and traditional international relations and longer, but he renewed discourse, especially after the transformation of the international system in the post-cold war and raised the question of sovereignty in the face of globalization that has characterized the global politics of the period and its aftermath, either at the domestic level, the State posed in front of renewed clashes jobs and strengthen the foundations of community unity and The Middle East is an important regional field for the study of the nature of the Arab private area who knew several transformations of the most prominent of the popular movement since 2011. Key words: Ginalogia, tyranny, tribal, sectarian, rentier state.